PELATIHAN PENYUSUNAN KTI MAHASISWA DALAM BIDANG KEOLAHRAGAAN - Arimbi Arimbi; Rusli Rusli; Sarifin G; Muhammad Nur; Andi Atssam Mappanyukki; Wahyana Mujari Wahid (Program Studi Ilmu Keolahragaan, 2022)
Writing scientific papers can simply be one of the requirements for completing a student's level of education or become a productive and useful hobby. A scientific work is actually the responsibility of academics in ensuring the development of knowledge from time to time. Writing scientific papers is not the same as writing non-scientific articles in general. Writing scientific papers means we make scientific research and can be accounted for. For this reason, writing scientific papers cannot be arbitrary, there are standard provisions that need to be followed, therefore, student understanding, especially in the scope of sports science related to the preparation of scientific papers, needs special attention so that they can produce good scientific papers that are oriented towards something. publication so that the scientific work that is made is widely useful in the community.